ANALYSIS OF THE PROJECT TO STRENGTHEN THE PANCASILA STUDENT PROFILE (P5) IN THE IMPLEMENTATION OF THE INDEPENDENT CURRICULUM IN HISTORICAL LEARNING AT SMK BUDI UTOMO PRAMBON: Analisis Projek Penguatan Profil Pelajar Pancasila (P5) Pada Pelaksanaan Kurikulum Merdeka Dalam Pembelajaran Sejarah Di SMK Budi Utomo Prambon - Maulidah Rahmawati; M. Faris Abdil Aziz; Satrio Wibowo (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This research aims to analyze the implementation of the Pancasila Student Profile Strengthening (P5) project in history learning at vocational schools (SMK) with a focus on the theme of local wisdom in traditional marriage. Using a descriptive qualitative approach, data was collected through observations, interviews, and documentation involving teachers and students at one vocational school. The results showed that integrating the theme of traditional marriage into the P5 project improved students' understanding of Pancasila values, such as community cooperation, diversity, and love for local culture. This project also successfully created active, collaborative, and contextual learning. Although there were some challenges such as limited resources and student motivation, these could be addressed through innovative teaching strategies and local community involvement. This research recommends strengthening collaboration between schools and communities as an effort to preserve culture and enhance student engagement.The Independent Curriculum includes the Pancasila Student Profile as a national learning objective, with its implementation requiring students to carry out projects to strengthen the Pancasila Student Profile, commonly abbreviated as P5.